Workers' cooperatives in Argentina: The Self-administered Workers' Association - Dobrusin, Bruno Nicolas (2013)
This article examines the development of the Self-administered Workers’ Association (Asociación Nacional de Trabajadores Autogestionados − ANTA) within the Workers’ Confederation of Argentina (Central de Trabajadores de la Argentina − CTA). ANTA is an organization that groups workers from different cooperatives, most of them originating in the post-2001 economic crisis in Argentina, when many small and medium-sized enterprises were rescued by their workers. It analyses how ANTA emerged as an organization within a trade union (CTA) and the dynamics of that relationship. This relationship is seen as one of the fundamental elements leading to the sustainability of the cooperatives. The article also examines the complexities of the relationship and the inadequacies in the development of the cooperative movement when associated with trade unions.